How Perceived Organizational Support for Environment Serves a Mechanism to Enhance Environmental Performance From Employee Perspective in Health Sector of Indonesia - Nugraha, Andhyka Tyaz; Iqbal, Muhammad (KINERJA, 2023)
Our study investigates the role of Green human resource management (GHRM) practices on the individual environmental performance of employees (IEP) as well as the mediating role of perceived organizational support (POS) in the health sector in Indonesia. Data was collected using a questionnaire that was shared with 310 nurses working in Indonesian as respondents. SmartPLS 3 software is used to analyze data by adopting the PLS-SEM approach. The research findings reveal a strong and positive relationship between the dimensions of GHRM practices such as Green Employee Involvement (GEI),  Green Management Performance (GMP), and Green Training (GT) on the individual environmental performance of employees in Indonesia's health sector. Furthermore, we also found an indirect effect of GHRM practices on employees' environmental performance through perceived environmental support from the organization company. Based on our study, we suggest Institutions and organizations in Indonesia's health sector concern implement GHRM practices to improve their employees' individual environmental performance. Specifically, our study extends the previous literature by exploring the relationship of GHRM practices with individual environmental performance using perceived organizational support (POS) as a mediating variable.